Analysis Of The Needs For An Inventory Information System For Land Asset Document Management At PT PLN UIT JBT - Fitriliani, Putri Angelina; Ramadhan, Gilang; Saleh, Suji Abdullah (Indonesian Accounting Research Journal, 2025)
PT. PLN (Persero) Central Java Transmission Main Unit manages many assets in the form of land to support the construction of towers. Assets managed are land assets consisting of land rights data, type of certificate, pre-certificate, mapping of land location, and documents on legal aspects of the land. These land assets included in regional property whose management must be accountable. However, this management is not optimal. To support inventory activities which contain land asset data, land asset mapping, and digital land asset documents. Based on the PIECES Framework analysis which consists of the dimensions Performance, Information and Data, Economic, Control and Security, Efficiency, and Service. This research was using descriptive research methods with a qualitative approach through data collection techniques of interviews. Developing the latest information system that is integrated, efficient and responsive to the needs for land asset document management is a strategic step.